VIth World Congress on Science and Football, Book of Abstracts, January 16-20, 2007, Antalya, Turkey - Poster Presentations - Sports Injuries and Prevention (Journal of Sports Science & Medicine, 2007)
Summaries on the following topics: P-046 Visual enriched presentation of football related injuries P-047 Creatine kinease and testosterone cortisol ratio in a competition soccer halfseason P-048 Knee functions in soccer players after anterior cruciate ligament reconstruction P-049 Injury statistics in a competitive football team P-050 Effect of long term soccer on spinal mobility and lumbar spine degeneration P-051 Biofeedback for improving weight-bearing following lower limb football injuries: A new assessment and rehabilitation device P-052 Percutaneous headless screw fixation in surgical treatment of jones fracture in professional football players P-053 Injury evaluation of Turkish national men`s football team P-054 Enthesis pain and growth height velocity curve in junior high school soccer players P-055 Learning condition and effectiveness of stretching in junior high school soccer players P-056 Medical support in Gunma Football Association U-18 tournaments: Role of physical therapist P-057 Effect of leg cooling at half time breaks on performance of soccer-simulated exercise in hot environment P-058 Magnetic resonance image in athlete with groin pain P-059 Athletic rehabilitation of soccer players with groin pain P-060 Effects of injury related de-training on gross motor performance in elite soccer players P-061 Influence of soccer specific fatigue on knee joint kinematics during dynamic landings P-062 Influence of soccer-specific fatigue on kinematics of kicking P-063 Injury survey of young competitive football players P-064 Spondylolysis in adolescent and pediatric soccer players P-065 Prevention of non-contact injuries in soccer